Utopia - Borgen, Trond; Borresen, Einar (Stavanger : Rogaland Kunstmuseum, 2000)
Christensen, Allan ; Copers, Leo ; Cronhammar, Ingvar ; Ekstrand, Anna-Maria ; Eriksen, Roar Werner ; Forced Entertainment Opera ; Gedin, Andreas ; Gormley, Antony ; Hamilton, Lova ; Johannessen, Kurt ; Kvium, Michael ; LaBelle, Charles ; Larsen, Yngvar ; Ma Liuming ; Nordling, Catherine ; Ostojic, Tanja ; Petry, Michael ; Rodland, Torbjorn ; Rosenmeier, Lisa ; Ruka, Inta ; Serck-Hanssen, Fin ; Tiffon, Agnès ; Zhang Huan
biog. per kunstenaar, ind. tent., gr. tent. p. 85-89
Noors & Engels
Utopia, Rogaland Museum of Fine Arts, Stavanger (Stavanger Museum), 09. September - 12. November 2000
boek